Decoding the Implications of Zinc in the Development and Therapy of Leukemia - Bo Zhu; Chunhao Yang; Siqi Hua; Kaiqiang Li; Pengyou Shang; Zhonghua Li; Wei Qian; Shunkang Xue; Qi Zhi; Zichun Hua (Advanced Science, 2025)
Abstract Zinc plays a central role in the hematological development. Therapeutic interventions with zinc are shown to improve the health status of patients with malignancies by stimulating the immune system and reducing side effects. Despite the abnormal zinc homeostasis in leukemia, the role and mechanisms of zinc signaling in leukemia development remain poorly understood. Recently, some important breakthroughs are made in laboratory and clinical studies of zinc in leukemia, such as the role of zinc in regulating ferroptosis and the effects of zinc in immunotherapy. Zinc‐based strategies are urgently needed to refine the current zinc intervention regimen for side‐effect free therapy in chemotherapy‐intolerant patients. This review provides a comprehensive overview of the role of zinc homeostasis in leukemia patients and focuses on the therapeutic potential of zinc signaling modulation in leukemia.